Application of Silver/Carbon-based Composite Nanofiber Membrane for Improvement of Microfiltration System - Tanayt Sinprachim; Kattinat Sagulsawasdipan; Somchai Sonsupap (Recent Science and Technology, 2025)
In this study, silver-reinforced carbon nanofiber membranes (CNF@Ag) were fabricated through a binder-free extrusion process. A precursor mixture of carbon nanofibers (CNF) and silver nitrate (AgNO₃) was extruded at 40 MPa, followed by sintering at 800°C in an argon atmosphere for 4 hours to enhance the membrane structure. The physical properties of the CNF@Ag membranes, including porosity, wettability, morphology, and microfiltration efficiency, were systematically analyzed. The results demonstrated that the CNF@Ag membranes exhibited effective microfiltration properties with pore sizes ranging from 9.21 to 21.99 nm. These membranes achieved a turbidity removal efficiency of up to 92.69%, indicating their potential as an effective pre-treatment step for seawater desalination. This study highlights the promising application of CNF@Ag membranes in water purification processes, particularly for turbidity removal in desalination systems.
Keywords: Membrane Separation Technologies; Electrospun Nanofibers in Biomedical Applications; Solar-Powered Water Purification Methods